The Influence of the Pancasila Student Profile Strengthening Project (P5) on the Development of Creativity among Fourth-Grade Students at SD Negeri 33 Pagaralam City - putri, Menthari Dwi Putri; Hendy Kariyanto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Based on preliminary observations conducted by the researcher in the fourth grade of SD Negeri 33 Pagar Alam City, several issues related to the development of students’ creativity were identified, such as the lack of teaching materials and tools used by teachers, the limited creative ideas from students, and the low enthusiasm of students in developing their creativity. These conditions affected students’ abilities to express ideas, solve problems, and build self-confidence. This study aimed to determine whether there is an influence of the Pancasila Student Profile Strengthening Project (P5) on the development of creativity among fourth-grade students. The research employed a descriptive quantitative method with data collected through observation, interviews, questionnaires, and documentation. Data analysis included validity tests, reliability tests, normality tests, linearity tests, hypothesis testing, and significance testing. The results showed that the t-count value (2.997) was greater than the t-table value (1.717) (t-table 5%, n = 22), and the significance value was 0.006 < 0.05. Therefore, it can be concluded that there is a significant influence of P5 on the development of creativity among fourth-grade students at SD Negeri 33 Pagar Alam City.